The strawberry blonde [videorecording (DVD)] - Walsh, Raoul, 1887-1980; Cagney, James, 1899-1986; De Havilland, Olivia; Hayworth, Rita, 1918-1987; Hale, Alan, 1892-1950; Hagan, James, approximately 1888-1947 (Archive collection., 2008)
Young Biff Grimes is the son of an Irishman who's better at blarney than at holding down a job. Determined to make something of himself, Biff takes a mail-order course in dentistry and practices his handiwork on dear old dad. In his spare time he manages to fall for Virginia Brush, "the strawberry blonde," but unfortunately Virginia is more interested in Hugo Barnstead, an up-and-coming financier. Virginia has another girl in mind for Biff: her best friend Amy, a suffragette with plenty of spunk.